International Refugee Law II: The 1951 United Nations Convention Relating to the Status of Refugees - Béres, Nóra (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
This chapter seeks to provide a brief overview on the Refugee Convention focusing on its two key elements, the refugee definition and the refugee status. Within the framework of this analysis, after discussing introductory issues such as the scope of international refugee law and the adoption and historical context of the Refugee Convention and its Protocol, the chapter also examines in detail the refugee definition (the inclusion, the exclusion and the cessation criteria) and the content of the refugee status. The refugee definition is a centrepiece of international migration law designating the potential beneficiaries of the refugee status, and by this designation, fulfilling the ultimate purpose of the Refugee Convention. Therefore, understanding the definition of refugees is crucial for seeing the broader context. The incremental nature of refugee rights is also an aspect that is worth analysing, thus the chapter devotes its last subchapter to this issue. Keywords: migration, non-refoulement, refugee convention, refugee definition, refugee status